The American campus kaleidoscope: Examining the academic and social experiences of international students - Kamran, Komal; Awan , Awais Ahmed Riaz (Journal of International Students, 2024)
This study explores the academic and social experience of international students in colleges in the United States of America. Specifically, the study focuses on colleges with a high percentage of international students as they represent diverse cultural backgrounds and contribute significantly to the campus environment. Data were collected from 30 participants (undergraduate students) across five focus group interviews and a thematic analysis was performed. For academic experience, four sub-themes emerged: relationship with professors, academic resources, liberal arts requirements; and class participation weightage. For social experience, four sub-themes emerged: role of student clubs and societies; inter-college collaborations; intercultural sensitivity; and religious/cultural events. Findings provide valuable implications on how colleges with a high population of international students can improve the academic and social experience of these students.